Aesthetic rehabilitation of anterior teeth after dental trauma using the BRB matrix technique and stratification - Case report (Research, Society and Development, 2023)
Cases of dental trauma are common in the dental office routine, which mostly affect children and adolescents. The main causes of injuries are sporting activities, falls, accidents and violence. Therefore, the present study aims to report a clinical case of fracture of the middle/incisal third of units 11 and 21, where direct restorations were performed in composite resin, using the BRB matrix technique through layering, employing the simplified system of Tetric N-Ceram composite resin. The BRB matrix technique consists of silicone molding of the initial clinical condition and direct wear on the mold itself, simulating the palatal shell and tooth contours. The main advantage of the technical option is that it is carried out in a single clinical session, eliminating the need for laboratory waxing procedures, providing lower costs and facilitating the construction of the functional characteristics of the palatal support, being of great clinical interest due to its practicality for both the patient and the dental surgeon. Finally, it was possible to restore the affected units efficiently, restoring the patient's aesthetics and function and minimizing the trauma that a fractured anterior tooth can cause.